Intestinal Flora: A Pivotal Role in Investigation of Traditional Chinese Medicine - Li, Xiao; Wu, Dan; Niu, Jingjie; Sun, Yanping; Wang, Qiuhong; Yang, Bingyou; Kuang, Haixue (The American journal of Chinese medicine (1979), 2021)
Intestinal flora is essential for maintaining host health and plays a unique role in transforming Traditional Chinese Medicine (TCM). TCM, as a bodyguard, has saved countless lives and maintained human health in the long history, especially in this COVID-19 pandemic. Pains of diseases have been removed from the effective TCM therapy, such as TCM preparation, moxibustion, and acupuncture. With the development of life science and technology, the wisdom and foresight of TCM has been more displayed. Furthermore, TCM has been also inherited and developed in innovation to better realize the modernization and globalization. Nowadays, intestinal flora transforming TCM and TCM targeted intestinal flora treating diseases have been important findings in life science. More and more TCM researches showed the significance of intestinal flora. Intestinal flora is also a way to study TCM to elucidate the profound theory of TCM. Processing, compatibility, and properties of TCM are well demonstrated by intestinal flora. Thus, it is no doubt that intestinal flora is a core in TCM study. The interaction between intestinal flora and TCM is so crucial for host health. Therefore, it is necessary to sum up the latest results in time. This paper systematically depicted the profile of TCM and the importance of intestinal flora in host. What is more, we comprehensively summarized and discussed the latest progress of the interplay between TCM and intestinal flora to better reveal the core connotation of TCM.